Pengaruh Soft Skill, Hard Skill Dan Pengalaman Magang Terhadap Kesiapan Kerja (Studi pada Mahasiswa Non Pendidikan Universitas PGRI Semarang) - Alfiana, Reza; Indiworo, Hawik Ervina; Darmaputra, M. Fadjar (Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to determine the influence of soft skills, hard skills and internship experience on the work readiness of non-educated students at PGRI University Semarang. This research uses multiple linear regression analysis methods. The number of samples used in this research was 248 respondents. The data collection technique uses a questionnaire and to test hypotheses using SPSS 24. Based on the results of this research, it shows that soft skills (X1), hard skills (X2) and internship experience (X3) simultaneously have a positive and significant effect on students' work readiness (Y) non-education PGRI University Semarang.